Shaping Children's Character in the Era of Revolution 4.0 and Society 5.0 as a Successor to the Nation through Early Childhood Education - Putri Loviana Aura Tahlia; Siti Maryam; Debby Adelita (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This research delves into character education by examining the techniques and factors influencing character building at Harapan Kita Condong Gading Probolinggo Kindergarten. It employs qualitative methods to explore how character formation strategies align with national objectives and contemporary demands within Early Childhood Education (ECE), particularly amidst the Revolution 4.0 and Society 5.0 era. Through in-depth interviews, observations, and document analysis involving educators, and children at TK Harapan Kita Condong Gading Probolinggo, the study seeks to understand their perspectives, experiences, and practices regarding character formation. Thematic analysis reveals key themes related to techniques such as outdoor activities, play-based learning, music, repetition, and reinforcement, along with the integration of technology like Internet of Things (IoT) to enhance character development. By uncovering effective strategies for character formation and addressing challenges faced by educators, this research contributes to our understanding of nurturing children's character in ECE settings, emphasizing the importance of holistic approaches that blend traditional values with innovative practices.